GAMBARAN SELF REGULATED LEARNING PADA MAHASISWA DITINJAU DARI BIDANG ILMU EKSAKTA DAN SOSHUM - Zadrian Ardi; Rahmi Dwi Febriani; Rima Pratiwi Fadli; Lathifa Khairah; Frischa Meivilona Yendi (LPPM Universitas Ekasakti, 2024)
This study is motivated by the observation that some students struggle to manage their time and study situations, often prioritizing activities that do not support their personal development. This indicates that students may have inadequate self-regulated learning. The objectives of this research are to describe: 1) the overall self-regulated learning of students, 2) the self-regulated learning of students in the exact sciences, 3) the self-regulated learning of students in the social sciences, and 4) to examine the differences in self-regulated learning between students in the exact sciences and social sciences. This research employs a quantitative approach with a comparative descriptive design. The sample consisted of 388 students selected using proportional random sampling. The instrument used was a self-regulated learning questionnaire that has been tested for validity and reliability. Data were analyzed using descriptive statistical techniques and t-test analysis with Microsoft Excel and SPSS 26. The findings reveal that: 1) the overall self-regulated learning of students is categorized as high; 2) the self-regulated learning of students in the exact sciences is categorized as high; 3) the self-regulated learning of students in the social sciences is categorized as moderate; and 4) there is a significant difference in self-regulated learning between students in the exact sciences and social sciences. The implications for counseling services that can be provided include informational services and group guidance.